0880 A Pilot Study Evaluating the Effect of Head Elevation During Sleep on Obstructive Sleep Apnea in Pre-Pubertal Children with Down Syndrome. (27th May 2020) - Kaplan, K; Spielberg, D; Petitto, L; Musso, M; Glaze, D
Abstract: Introduction: Children with down syndrome are at high risk for developing obstructive sleep apnea when compared to typically developing children. Treatment of obstructive sleep apnea is complicated as these children often struggle with traditional therapies such as positive airway pressure. In adult populations it has been shown that head elevation is successful in reducing the severity of OSA (AHI). The hypothesis of this study is that head elevation (30°) would improve OSA in a cohort of pre-pubertal children with down syndrome. Methods: Children with down syndrome, aged 4-13, presenting to the sleep clinic at Texas Children's Hospital were screened for enrollment into the study (n=21; 11 male). Subjects were randomized to begin a diagnostic polysomnogram with either the head of the bed flat (0°) or elevated (30°). Head position was alternated every 2 hours during the study. Studies were performed in an AASM pediatric sleep center by a registered PSG technologist. Studies were scored using AASM pediatric scoring rules. Data was analyzed using paired student t-tests. Each subject served as their own control. Results: There was no significant difference in AHI (p=0.71), RDI (p=0.7), O2 nadir (p=0.17), total sleep time (p=0.34), sleep efficiency (p=0.28), time in REM sleep (p=0.94) or arousal index (p=0.14) when the head of the bed was flat (0°) versus elevated (30°). The study shows that head elevation is not successful in significantly reducing obstructive sleep apnea in a pre-pubertal pediatric population of children with down syndrome. Conclusion: In children with down syndrome, aged 4-13, referred for a diagnostic sleep study, there is no improvement in OSA due to head elevation (30°) when compared to sleeping flat (0°). These findings were independent of if the subject started with the head of the bed flat or elevated. Other cofounders were eliminated as each subject served as their own control. Support: No external funding was utilized for this study.